ChemInform Abstract: Rhodium‐Catalyzed Tandem Hydroformylation/Arylation Reaction with Boronic Acids. Issue 39 (23rd September 2014) - Almeida, Ana R.; Dias, Roberto D.; Monteiro, Carlos J. P.; Abreu, Artur R.; Gois, Pedro M. P.; Bayon, J. Carles; Pereira, Mariette M.
Abstract A rhodium/triphenylphosphine catalytic system is employed for the tandem hydroformylation/arylation reactions of aryl olefins to give branched secondary alcohols with high regioselectivity.